Editorial - 7th International Students Summer School on Human Growth - Data Analysis and Statistics - Detlef Groth; Michael Hermanussen; Christiane Scheffler (Human Biology and Public Health)
Statistics is the key skill required by reseachers to answer scientific questions based on often complex data sets. 9 students and young researchers from Indonesia, South Africa, Spain, Slovakia, and Germany were educated and trained on their own data sets with the aim to publish these results at the 7th International Students Summer School on Human Growth - Data Analysis and Statistics at the Ecological Station Gülpe of the University of Potsdam from July 3rd to 11th 2024.